The Influence of Peers on Learning Motivation Class X Hospitality Student at SMK N 9 Padang - Kisyan Dewi, Cerly; Fitria, Linda; Menrisal , M (SAFE-Network, 2024)
This study aims to determine the influence of peers on learning motivation of students in class X Hospitality SMK 9 Padang Semester Even in the 2021/2022 academic year. This type of research is descriptive quantitative correlational research with a population of 204 respondents, and the sample is taken using the proportional random sampling method so that the sample obtained is 135 respondents. The instrument used in this research is a questionnaire compiled according to the Likert Scale model. The type of data in this study is primary data obtained from SMK N 9 Padang. The analytical tools used are Microsoft Excel 2010 and SPSS version 20. Based on the research that has been carried out with the results of the calculated hypothesis, the rcount value is 0.222 while the rtable value is 0.169 because the rcount value is greater than the rtable value (0.222 > 0.169) it can be concluded that